FLORISTIC STUDY IN THE LOWER PAPAGAYO RIVER BASIN, GUERRERO, MEXICO - Blanca Estela Carreto-Pérez; Ángel Almazán-Juárez; Pablo Sierra-Morales; R. Carlos Almazán-Núñez (Polibotánica, 2015)
We present the floristic composition of the Papagayo river basin, Guerrero, México.Field work was carried out from June 2011 to June 2012. We identified a total of 204 species of vascular plants, including 73 families and 163 genus. Families Fabaceae,Poaceae, Asteraceae, Euphorbiaceae and Rubiaceae represented 41% of all species and 38% of the genus in the study area. The herbaceous plant life form was the best represented with 81 species (40%). Were determined 10 vegetation types, of which the tropical deciduous forest covers the largest area and has the richest flora. Eleven species were recorded under the category of threatened by NOM-059-SEMARNAT-2010, of which one is endemic to Mexico (Rhizophora mangle).